Fundamental of Computer Problem Solving (CSC 128) – final exam format and frequent questions / Azlina Mohd Mydin, Wan Anisha Wan Mohammad and Naemah Abdul Wahab - Mohd Mydin, Azlina Mohd Mydin; Wan Mohammad, Wan Anisha; Abdul Wahab, Naemah (Unit Penerbitan JSKM, 2020)
Fundamental of Computer Problem Solving (CSC 128) is one of the servicing papers offered in UiTM for diploma students. The subject is taken by student from mechanical engineering, civil engineering, actuarial science and statistic. This course contains three (3) credit hours with two (2) hours for lecturing and another two (2) hours for lab session. The main purpose of this paper is to introduce problem solving using computers. It also emphasizes various aspects of problem solving, phases of problem solving and basic techniques in designing a solution using C++ language. CSC128 also emphasis on solving problems using computer rather than the syntactical aspects of the chosen programming language which is C+ +.